JURIDICAL REVIEW OF THE STRENGTH OF THE SALE AND PURCHASE AGREEMENT ACT IN LAND RIGHTS TRANSFER TRANSACTIONS - I Gusti Putu Adi Abdi Yasa; I Made Mulyawan Subawa; I Gusti Agung Ika Laksmi Mahadewi (International Journal of Business, Law and Political Science, 2026)
Objective: This study aims to analyze the legal standing and binding strength of the PPJB Deed in land rights transfer transactions, as well as to analyze the legal protection for the parties involved in a PPJB executed after tax obligations have been fulfilled. Method: This study is a normative legal research utilizing a statutory approach and a conceptual approach, supported by primary, secondary, and tertiary legal materials collected through a literature review and analyzed qualitatively. As the analytical framework, the theory of the rule of law, the theory of legal certainty, the theory of legal protection, and the theory of contract are applied to examine the issues formulated in this research. Results: The results of the study indicate that the PPJB deed is a preliminary agreement that is obligatory, valid, and binding upon the parties, and possesses evidentiary value as an authentic deed, yet it does not result in the legal transfer of land rights. Legal protection for the parties is realized through the drafting of the PPJB by a Notary, the fulfillment of BPHTB and Income Tax (PPh) obligations, and the satisfaction of administrative requirements prior to the execution of the AJB. Novelty: Issues arise due to tax regulations specifying that the PPJB serves as the basis for when the Land and Building Title Transfer Tax (BPHTB) becomes due, whereas the legal transfer of rights only occurs after the AJB is executed and registered.